EFEKTIVITAS MODEL PEMBELAJARAN HUITT DENGAN MEDIA QUESTION CARD DAN MODEL PEMBELAJARAN PQ4R DENGAN MEDIA FLIP BOO MAKER TERHADAP HASIL BELAJAR LOGIKA MATEMATIKA SISWA KELAS X SMA NEGERI 1 SEMARANG - Sri Kadarwati; Suparman -; Nurmawati - (Jurnal Karya Pendidikan Matematika, 2015)
Mathematics is a subject often considered difficult by students from the elementary level, junior, arrived at the high school level Math, this is because it deals with things that are abstract. Therefore teachers of mathematics in learning is expected to have a good mastery, can select the appropriate learning strategies, as well as using the learning models that can improve student learning and student motivation can be moreactive in learning. With that in mind it was all finally can improve student learning outcomes.The fact shows that learning mathematics on Logic X-grade material in SMA Negeri Semarang teachers I still dominate the learning, the students seemed passive and just accept the knowledge provided by the teacher. In addition teachers not to use media learning, not to use the strategies and methods that can enable students so the students understanding of the material is still low. In order to overcome passivity and lack of understanding of students of class X in addition Logic material model Huitt learning with media Question cards and learning model PQ4R with media Flip Book Maker.Through two models this will be seen pempelajaran keektifan students so that they can improve student learning outcomes.This research uses a type of experiment using two classes of experimental and one control class. As the population in this research is the whole grade X which consists of 8 classes, and then randomly selected three classes. One class as a class that implements the I model experiment study of Huitt with media Question cards, a class again as a class that implements the model II experimental learning PQ4R with media Flip Book Maker, as well as one other the rest of the class as the class of the control.Data processing using statistics "(test of normality, test, and test homoginitas ANAVA).The purpose of this study is to: 1) see any difference whether or not the results studied mathematics students who got media learning model Huitt with Question cards, a learning model with a Flip Book PQ4R media Maker, and the learning model Ekospositori, 2) look at the effectiveness of the learning model Huitt with media Question cards, a learning model with a Flip Book PQ4R media Maker, and Ekospositori learning models at sub subject of mathematical logic in the lesson 20142015.From the results of the study indicate that there is a difference between the results of the study of mathematics students who got media learningmodel Huitt with Question cards, a learning model with a Flip Book PQ4R media Maker, model and learning Ekospositori learning more effective, and there is a difference in student learning results in mathematical logic in teaching 2014-2015.Keywords: learning Huitt, PQ4R, Question cards, Flip Book Maker.